2006
DOI: 10.1002/jca.20043
|View full text |Cite
|
Sign up to set email alerts
|

Blood component collection by apheresis

Abstract: Apheresis component collection is a rapidly growing area in the blood collection field. Several instruments with varying capabilities are available. This is a brief review of the equipment available for granulocyte and apheresis component collection and indications for their use. In the United States, granulocytes are collected with the Fenwal CS3000, Fenwal CS3000 Plus, COBE (Gambro) Spectra, Haemonetics LN9000, and Fresenius AS 104. The use of hetastarch for sedimenting agent and stimulation with G-CSF and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 24 publications
1
57
0
Order By: Relevance
“…Haemonetics collects whole blood into a spinning centrifuge bowl, and then either plasma or PAS is pumped into the bottom of the bowl to push the supernatant platelets into a collection bag for storage. 7 The Spectra has a dual-stage processing channel with the red and white cells removed in the first stage, and the platelets are concentrated in the second stage followed by transfer to a storage bag. 7 The Trima has a single-stage channel where the cells separate into layers according to specific gravity, and each component leaves by its own outlet into a storage bag.…”
Section: Experimental Designmentioning
confidence: 99%
“…Haemonetics collects whole blood into a spinning centrifuge bowl, and then either plasma or PAS is pumped into the bottom of the bowl to push the supernatant platelets into a collection bag for storage. 7 The Spectra has a dual-stage processing channel with the red and white cells removed in the first stage, and the platelets are concentrated in the second stage followed by transfer to a storage bag. 7 The Trima has a single-stage channel where the cells separate into layers according to specific gravity, and each component leaves by its own outlet into a storage bag.…”
Section: Experimental Designmentioning
confidence: 99%
“…According to these reports, the single-needle Amicus and single-needle Trima Accel have the highest CE and CR [3,8,9,10,58]. Flesch et al [21] reported that the double-needle Amicus and the single-needle Trima Accel showed similar platelet yields and donation times.…”
Section: Donor Screening For Plateletpheresismentioning
confidence: 99%
“…Negatively charged platelet surfaces promote the activation of coagulation factors II and X [8,39]. Various studies have investigated platelet activation, which has been used to evaluate platelet quality during processing and storage of plateletpheresies products.…”
Section: Platelet Activationmentioning
confidence: 99%
See 2 more Smart Citations